2001
DOI: 10.1021/ic001245f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electrochemistry, and Spectroscopic Characterization of Bis-dirhodium Complexes Linked by Axial Ligands

Abstract: The synthesis and electrochemical and spectroscopic properties of bis-dirhodium complexes containing ap or dpf bridging ligands, (ap)(4)Rh(2)(C triple bond C)(2)Rh(2)(ap)(4) (2) and (dpf)(4)Rh(2)(CNC(6)H(4)NC)Rh(2)(dpf)(4) (4), were investigated (where ap and dpf are the 2-anilinopyridinate and N,N'-diphenylformamidinate ions, respectively). The related "simple" dirhodium species, (ap)(4)Rh(2)(C triple bond C)(2)Si(CH(3))(3) (1) and (dpf)(4)Rh(2)(CNC(6)H(5)) (3), with the same set of bridging ligands were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…Only a bidentate ligand 1,4-diisocyanobenzene (1,4-dib) with longer NC ligating arms from a benzene ring (Scheme 3) can coordinate to the Rh ion through the axial crowded space, giving a polymer complex [Rh 2 (4-Me-pf) 4 (1,4-dib)] n , which was isolated from the benzene and toluene solution [28,29]. A hexanuclear complex [{Rh 2 (4-Mepf) 4 } 3 (1,4-dib) 2 ] was isolated from the dichloromethane solution [28], while a tetranuclear complex [{Rh 2 (dpf) 4 } 2 (1,4-dib)] (dpf -= N,N'-diphenylformamidinate anion) was also isolated from dichloromethane solution [30]. We preliminarily showed that pyz could work as a linker ligand for cis-[Rh 2 (R-pf) 2 (O 2 CCF 3 ) 2 ] with less crowded axial sites compared with [Rh 2 (R-pf) 4 ] based on the crystal structure of [Rh 2 (4-Et-pf) 2 (O 2 CCF 3 ) 2 (pyz)] n •n(toluene) (4-Et-pf -= N,N'-bis(4-ethylphenyl)formamidinate anion), such a study has not been performed since then [31].…”
Section: Introductionmentioning
confidence: 99%
“…Only a bidentate ligand 1,4-diisocyanobenzene (1,4-dib) with longer NC ligating arms from a benzene ring (Scheme 3) can coordinate to the Rh ion through the axial crowded space, giving a polymer complex [Rh 2 (4-Me-pf) 4 (1,4-dib)] n , which was isolated from the benzene and toluene solution [28,29]. A hexanuclear complex [{Rh 2 (4-Mepf) 4 } 3 (1,4-dib) 2 ] was isolated from the dichloromethane solution [28], while a tetranuclear complex [{Rh 2 (dpf) 4 } 2 (1,4-dib)] (dpf -= N,N'-diphenylformamidinate anion) was also isolated from dichloromethane solution [30]. We preliminarily showed that pyz could work as a linker ligand for cis-[Rh 2 (R-pf) 2 (O 2 CCF 3 ) 2 ] with less crowded axial sites compared with [Rh 2 (R-pf) 4 ] based on the crystal structure of [Rh 2 (4-Et-pf) 2 (O 2 CCF 3 ) 2 (pyz)] n •n(toluene) (4-Et-pf -= N,N'-bis(4-ethylphenyl)formamidinate anion), such a study has not been performed since then [31].…”
Section: Introductionmentioning
confidence: 99%
“…Highly unsaturated, rigid -(C"C) n -and -(C@C) n -bridges offer an extended p-system and have been recognized as being particularly efficient in mediating electronic transfer [5][6][7][8][9][10]. In this context, a vast number of mono-and bimetallic complexes with polyynediyl or polyacetylene bridges have been extensively studied [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. For example, as model complexes to aid understanding of the influence of substituents on the bonding properties within the metal-acetylide backbone, mononuclear metal r-arylacetylides [(g 2 -dppe)(g 5 -C 5 Me 5 )M(C"C)-1,4-(C 6 H 4 )X] (M = Fe or Ru) have recently been reported by Paul and Bruce et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray studies revealed the formation of a CARh bond, a structural analog of rhodium carbenoids [21][22][23]. For example, rhodium(II) tetraacetate forms with phenylisonitrile an 1:2 adduct, appearing as yellow crystals [22].…”
Section: Spectroscopic Investigationsmentioning
confidence: 99%